OP0105 EFFICACY AND SAFETY OF BIMEKIZUMAB IN ANKYLOSING SPONDYLITIS: 48-WEEK PATIENT-REPORTED OUTCOMES FROM A PHASE 2B, RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED, DOSE-RANGING STUDY. (2nd June 2020) - Van der Heijde, D.; Gensler, L. S.; Deodhar, A.; Baraliakos, X.; Poddubnyy, D.; Kivitz, A.; Farmer, M. K.; Baeten, D.; Goldammer, N.; Coarse, J.; Oortgiesen, M.; Dougados, M.
Abstract : Background: Bimekizumab (BKZ), a monoclonal antibody that selectively neutralises interleukin (IL)-17A and IL-17F, is a potential therapeutic option in ankylosing spondylitis (AS). Objectives: To report 48-week (wk) patient-reported outcomes (PROs) in patients (pts) with AS treated with BKZ in a phase 2b dose-ranging study (BE-AGILE; NCT02963506 ). Methods: Pts with active AS (Bath AS Disease Activity Index [BASDAI] ≥4; spinal pain ≥4 [0–10]), fulfilling modified New York criteria (central reading), and inadequate response/intolerance to NSAIDs were randomised according to the study design (Figure 1 ). PROs included spinal pain, fatigue (BASDAI Q1), morning stiffness (mean of BASDAI Q5 + 6), Bath AS Functional Index (BASFI), Medical Outcomes Study (MOS) Sleep Problems Index II and AS Quality of Life questionnaire (ASQoL). Efficacy is reported for pts initially randomised to placebo (PBO) or BKZ 160/320 mg every 4 weeks (Q4W); treatment-emergent adverse events (TEAEs) are reported for pts who received ≥1 dose of study drug (Safety Set). Results: Of 303 pts, 181 were randomised to PBO or BKZ 160/320 Q4W mg at Wk 0; 179/181 completed Wk 12 and 161/181 completed Wk 48. At Wk 12, improvements in pain, fatigue, morning stiffness, BASFI, sleep and ASQoL were greater in BKZ pts vs PBO pts. Responses were further improved or maintained to Wk 48, with no meaningful differences between BKZ 160 mg and 320 mg (Table 1 ). Serious TEAEs occurred in 13/303 (4.3%) pts (Table 2 ), which included 2 major adverse cardiac events considered not related to study drug. Oral candidiasis occurred in 16 (5.3%) pts. Conclusion: Pts with active AS demonstrated rapid and sustained improvements in PROs, sleep and quality of life over 48 wks of BKZ treatment. BKZ was generally well tolerated with no unexpected safety findings versus previous studies. Acknowledgments: This study was funded by UCB Pharma. Editorial services were provided by Costello Medical. Disclosure of Interests: Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Lianne S. Gensler Grant/research support from: Pfizer, Novartis, UCB, Consultant of: AbbVie, Eli Lilly, GSK, Novartis, UCB, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Mary Katherine Farmer Employee of: UCB Pharma, Dominique Baeten Employee of: UCB Pharma, Nadine Goldammer Employee of: UCB Pharma, Jason Coarse Employee of: UCB Pharma, Marga Oortgiesen Employee of: UCB Pharma, Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma